Gc- ms analysis of ethyl acetate extract of sterptomyces species isolated From vermicast - R. BALACHANDAR,; K. ASHOK KUMAR,; N. KARMEGAM, (International Journal of Pharma and Bio Sciences, 2016)
In this study, the bioactive compounds present in the ethyl acetate extracts of two different Streptomyces strains isolated from vermicast (earthworm fecal pellets) were investigated using Gas Chromatography and Mass Spectrometry (GC-MS). GC-MS analysis showed the presence of 12 and 9 bioactive compounds in AS1 and AS3 respectively. GC-MS analysis of AS1extract revealed the presence of major bioactive compounds such as n-hexadecanoic acid, 6-hexadecanoic acid, methyl ester, 9-octadeconic acid, methyl ester, 2-4, cycloheadien-1-one, 3,5-bis (1,1-dimethyl ethyl) 4-hydroxy and AS3 extract contains hexadecanoic acid, 9-octadecanic acid-E, oleic acid, 6-ocatadecanic acid, 2-4, cycloheadien-1-one, 3,5-bis (1,1-dimethyl ethyl) 4-hydroxy, 1,2-Benzisothiazol-3- amine tbdms, hexamethyl cyclotrisiloxane and 1,2-Bis (trimethylsilyl) benzene.